2017
DOI: 10.1089/neu.2016.4502
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness Changes and Their Relationship to Dual-Task Performance following Mild Traumatic Brain Injury in Youth

Abstract: Mild traumatic brain injury (mTBI) is common in youth, especially in those who participate in sport. Recent investigations from our group have shown that asymptomatic children and adolescents with mTBI continue to exhibit alterations in neural activity and cognitive performance compared with those without a history of mTBI. This is an intriguing finding, given that current return-to-learn and return-to-play protocols rely predominately on subjective symptom reports, which may not be sensitive enough to detect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 62 publications
1
39
2
Order By: Relevance
“…In CINP patients, decreased precuneus thickness coincided with worse performance on the TMT part B, however decreased cortical thickness and worse cognitive performance could not be revealed in CINP patients compared with controls. The observed association between working memory capacity and cortical thickness in CINP patients is in line with studies reporting associations between regional GM morphology and working memory capacity or other features of cognition in patients with fibromyalgia (Luerding et al, 2008), patients with complex regional pain syndrome (Lee et al, 2015), and in mild TBI patients (Urban et al, 2017).…”
Section: Decreased Cortical Thickness In the Precuneus: Associationsupporting
confidence: 89%
“…In CINP patients, decreased precuneus thickness coincided with worse performance on the TMT part B, however decreased cortical thickness and worse cognitive performance could not be revealed in CINP patients compared with controls. The observed association between working memory capacity and cortical thickness in CINP patients is in line with studies reporting associations between regional GM morphology and working memory capacity or other features of cognition in patients with fibromyalgia (Luerding et al, 2008), patients with complex regional pain syndrome (Lee et al, 2015), and in mild TBI patients (Urban et al, 2017).…”
Section: Decreased Cortical Thickness In the Precuneus: Associationsupporting
confidence: 89%
“…Morphometric investigations of the brain post-TBI were not limited to the volume of cortical regions, but also the cortical thickness. There were fewer investigations of cortical thickness, but early post-injury studies showed regions of dorso-lateral prefrontal cortex (dlPFC; McCauley et al, 2010; Urban et al, 2017; Wilde et al, 2011) and other prefrontal regions (McCauley et al, 2010; Wilde et al, 2011) as well as superior temporal sulcus (STS; McCauley et al, 2010; Wilde et al, 2011), cingulate regions (McCauley et al, 2010) and regions of the inferior parietal lobule (iPL; Urban et al, 2017) to be significantly thinner in the TBI group compared to controls. However, these differences were not replicated at a later timepoint post injury (Bigler et al, 2016) This is not to say that these differences have ‘recovered’ over time (due to the cross-sectional nature of this evidence) but more likely due to differences in methodology and samples.…”
Section: Resultsmentioning
confidence: 99%
“…This atrophy can vary in relation to injury factors such as mechanism, severity and pathology (Bigler, 2013; Cullen et al, 2011; Maxwell et al, 2010). This can be realised as changes to both brain volume (Bigler, 2016) and cortical thickness measures (Urban et al, 2017). Morphometric brain changes are also a feature of typical brain developing throughout childhood and adolescence (Batalle, Edwards and O'Muircheartaigh, 2018; Mills et al, 2016; Raznahan et al, 2011; Shaw et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical work using optogenetics to stimulate neuronal (electrical) activity has shown that this promotes adaptive myelination ( 85 ), and a recent human study has proposed that there is a strong link between neural connectonomics, their dynamics, and cortical white matter structure [or “myeloarchitecture” ( 67 )]. It seems reasonable to posit, given these findings, that our observations in altered connectivity of cortical ICNs could be related to neuromorphological changes ( 86 ), and more specially microscopic white matter pathology following concussion, including demyelination and/or differentiation ( 87 , 88 ), reductions in cortical thickness ( 89 91 ), and Wallerian degeneration ( 92 , 93 ).…”
Section: Discussionmentioning
confidence: 88%